2017
DOI: 10.12693/aphyspola.132.1579
|View full text |Cite
|
Sign up to set email alerts
|

Positronium Formation in Nanostructured Metals

Abstract: Positronium formation in Au films was studied using a magnetically guided continuous slow positron beam with variable energy. Black Au film with porous morphology was compared with conventional smooth Au film. In the smooth Au film positronium is formed on the film surface only. The black Au film exhibits porous sub-surface region containing micro-cavities interconnected with surface. Positronium is formed on inner surfaces of microcavities in the sub-surface region and travels through interconnected cavities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…BM films of various elements are deposited usually by thermal evaporation in carefully adjusted low pressure (∼ 100 Pa) of N 2 gas [7,8]. It has been reported that BMs can be prepared also by magnetron sputtering in Ar with small amount of N 2 [6][7][8][9][10]. In the growth of metallic films in PVD systems contamination from residual atmosphere should be considered [11].…”
Section: Introductionmentioning
confidence: 99%
“…BM films of various elements are deposited usually by thermal evaporation in carefully adjusted low pressure (∼ 100 Pa) of N 2 gas [7,8]. It has been reported that BMs can be prepared also by magnetron sputtering in Ar with small amount of N 2 [6][7][8][9][10]. In the growth of metallic films in PVD systems contamination from residual atmosphere should be considered [11].…”
Section: Introductionmentioning
confidence: 99%